Perusahaan Sektor Telekomunikasi Bangkrut? Analisis dan Evaluasi Model - Ariawan Ariawan; Eka Zahra Solikahan (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study aims to reveal whether the telecommunication sector company is bankrupt by using the Altman Z-Score, Zmijewski and Springate models and to measure which model provides a good level of accuracy in predicting bankruptcy. Using quantitative methods with a quantitative descriptive approach. The research data was taken from the financial statements of 5 companies in the telecommunications sector for the period 2013-2017. The results showed that the telecommunications sector companies have the potential to go bankrupt based on the measurement results of the Altman Z-Score, Zmijewski and Springate models. The best model used in predicting bankruptcy is the Zmijewski compared to the Altman Z-Score and Springate.